2016
DOI: 10.1007/s10489-016-0779-x
|View full text |Cite|
|
Sign up to set email alerts
|

A mathematical model for solving fully fuzzy linear programming problem with trapezoidal fuzzy numbers

Abstract: In this paper, an efficient method is introduced to solve fully fuzzy linear programming problems. The proposed method is derived from the multi-objective linear programming problem and lexicographic ordering method. Theoretical analysis for the proposed method has been provided. Moreover, some numerical experiments are given to show the preference of the proposed methods and are compared with some available methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…To make this property hold for the fuzzy case, it is necessary that the order relation ≼ establish a complete order on R ( ). To this aim, several authors, for example, 11,17,[24][25][26][27][28] have defined the order relation ≼ lexicographically by using a set of three or four ranking indices, guaranteeing to meet at least properties 1 to 4. However, in the existing methods, such an order relation has been used only to compare objective function values, mostly in FFLP problems having only equality constraints.…”
Section: Lexicographic Methods For Solving Fflp Problems With Inequamentioning
confidence: 99%
See 2 more Smart Citations
“…To make this property hold for the fuzzy case, it is necessary that the order relation ≼ establish a complete order on R ( ). To this aim, several authors, for example, 11,17,[24][25][26][27][28] have defined the order relation ≼ lexicographically by using a set of three or four ranking indices, guaranteeing to meet at least properties 1 to 4. However, in the existing methods, such an order relation has been used only to compare objective function values, mostly in FFLP problems having only equality constraints.…”
Section: Lexicographic Methods For Solving Fflp Problems With Inequamentioning
confidence: 99%
“…To handle fuzzy inequality constraints, some authors suggest to transform them into equalities by introducing nonnegative fuzzy slack and surplus variables 7,11,29,30 ; this is, however, incorrect as shown by Bhardwaj and Kumar 31 and Gupta et al 32 Other authors, for example, 6,8,14,26,33 use a partial order to handle the fuzzy inequality constraints and a linear ranking function or lexicographic ranking criterion with the objective function. Thus, it can be observed that, for both approaches in the literature, two different order relations are used for the inequality of fuzzy numbers in the same problem.…”
Section: Lexicographic Methods For Solving Fflp Problems With Inequamentioning
confidence: 99%
See 1 more Smart Citation
“…When the parameters and decision variables are fuzzy, the problem is formulated as a Fully Fuzzy Lineal Programming Problem (FFLP). There are many methodologies of solution to a FFLP [12]. Mostly of them, convert the original fuzzy model in a classical satisfactory model.…”
Section: E Fully Fuzzy Linear Programmingmentioning
confidence: 99%
“…An algorithm to solve the FFLP problem based on a new lexicographic ordering on triangular fuzzy numbers is suggested by Ezzati et al [17]. An efficient method to solve FFLP is introduced by Das et al [18]. Some well-known approaches for solving FLP problems is reviewed by Skandari and Ghaznavi [19] and some of their difficulties is shown by some numerical examples.…”
Section: Introductionmentioning
confidence: 99%